Nonaccidental Trauma Managed with Open Spinal Fixation and Instrumentation and a Review of the Literature - Gigliotti, Michael J.; Farou, Noa; Savaliya, Sandip; Rizk, Elias (Indian Journal of Neurotrauma, 2021)
Nonaccidental trauma (NAT), causing spinal injury is rare and occurs in up to 3% of cases. Management of these injuries is typically conservative, and thus surgical management is not widely reported in the literature. In this case report, we presented three patients to review the effectiveness of spinal instrumentation and posterior fusion in pediatric patients due to NAT. All patients recovered well and were neurologically intact at last follow-up with no postprocedural complications noted. Spinal arthrodesis is a safe, effective way to manage spinal injuries due to NAT in cases of fracture-dislocation, distraction injuries, as well as cases involving neurologic compromise.
Keywords: nonaccidental trauma; fusion; spinal injury; trauma